Diagnostic criteria and symptom grading for delayed gastric conduit emptying after esophagectomy for cancer: international expert consensus based on a modified Delphi process. Issue 4 (11th October 2019) - Konradsson, M; van Berge Henegouwen, M I; Bruns, C; Chaudry, M A; Cheong, E; Cuesta, M A; Darling, G E; Gisbertz, S S; Griffin, S M; Gutschow, C A; van Hillegersberg, R; Hofstetter, W; et al.
Abstract: Delayed gastric conduit emptying (DGCE) after esophagectomy for cancer is associated with adverse outcomes and troubling symptoms. Widely accepted diagnostic criteria and a symptom grading tool for DGCE are missing. This hampers the interpretation and comparison of studies. A modified Delphi process, using repeated web-based questionnaires, combined with live interim group discussions was conducted by 33 experts within the field, from Europe, North America, and Asia. DGCE was divided into early DGCE if present within 14 days of surgery and late if present later than 14 days after surgery. The final criteria for early DGCE, accepted by 25 of 27 (93%) experts, were as follows: >500 mL diurnal nasogastric tube output measured on the morning of postoperative day 5 or later or >100% increased gastric tube width on frontal chest x-ray projection together with the presence of an air–fluid level. The final criteria for late DGCE accepted by 89% of the experts were as follows: the patient should have 'quite a bit' or 'very much' of at least two of the following symptoms; early satiety/fullness, vomiting, nausea, regurgitation or inability to meet caloric need by oral intake and delayed contrast passage on upper gastrointestinal water-soluble contrast radiogram or on timed barium swallow. A symptom grading tool for late DGCE was constructed grading each symptom as: 'not at all', 'a little', 'quite a bit', or 'very much', generating 0, 1, 2, or 3 points, respectively. For the five symptoms retained in the diagnostic criteria for late DGCE, the minimum score would be 0, and the maximum score would be 15. The final symptom grading tool for late DGCE was accepted by 27 of 31 (87%) experts. For the first time, diagnostic criteria for early and late DGCE and a symptom grading tool for late DGCE are available, based on an international expert consensus process.